PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP PERINGKAT OBLIGASI (Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia 2011–2016) - Aditya Pratama, 13.05.52.0172; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2017)
This study aims to determine the effect of Profitability, Leverage, Liquidity and Size of the Company to the rating of bonds on non – financial companies listed on the stock exchange and rating bond issued by PT.PEFINDO. Sampling method using purposive sampking woth research period year 2011 until 2016. Relationship and or influence between variables is explained by using method of doubled linier regression analysis. This tudy consists of 1) Profitability has no effect 2) Levarage has asignificant negative effect 3) Liquidity does not affect the rating of bonds 4) The size of the company has a positive effect on the rating of bond.Keywords: Bond Rating, Profitability, Levergae, Liquidity, Size